Synthesis and Characterization of Lanthanide(III) Complexes of N,N’-Diethyleneamine-bis(3-carboxypropenamide) - Babu, N. (Asian Journal of Chemistry, 2016)
Ten complexes of lanthanides with a polydentate ligand N,N'-diethyleneamine-bis(3-carboxypropenamide) (DBCPH2) have been synthesized and characterized by elemental analysis, conductance and magnetic measurements, infrared spectral and thermal analysis. The thermal analysis of the complexes proves the presence of two molecules of coordinated water molecules. The complexes have been assigned the formula [LnL·2H2O] where Ln = lanthanide ions and L = [DBCP]2–. In these complexes the ligand acts as pentadentate.